Spatial concentration of the Social Determinants of Health in the Luján river basin, Province of Buenos Aires, Argentina (Huellas, 2018)
The analysis of the spatial concentration of the dimensions of Health Social Determinants (HSD) is part of a clear approach to understanding and interpreting the spatial distribution of social vulnerability to diseases from a geographical perspective. Through quantitative spatial analysis with Geographic Information Systems (GIS), aspects of the spatial distribution and spatial association of the observed data are addressed with the aim of producing a synthesis that might become a planning tool. In this way, the application of combined methodologies, such as the calculation of Global Spatial Concentration Indexes (GSCI), the Areal Spatial Concentration Indexes (ASCI), together with graphical representations using the Lorenz concentration curve and the map of spatial autocorrelation clusters, help to define areas that group spatial units in which the main population problems are made evident. The final result is presented as a tool that supports the territorial decision-making process for the management of the study area.
Keywords: Spatial Concentration; Spatial Distributions; Quantitative Geography; Geographical Information Systems (GIS); Lujan river basin